Artificial Intelligence Learning in Higher Education - Rompas, Parabelem Tinno Dolf; Winowatan, Saruendo; Binoli, Sri Astuti; Limeri, Hendrik; Batmetan, Johan Reimon (JR Education, 2025)
The development of Artificial Intelligence (AI) has introduced new opportunities for transforming higher education, particularly in digital learning, academic management, and scientific research. AI enables real-time learning data analysis, personalized learning materials tailored to student needs, and automation of administrative tasks. This structured literature review explores AI implementation, benefits, and challenges in higher education. The findings indicate that adaptive learning systems, learning analytics, intelligent tutoring systems, and AI-driven chatbots enhance learning effectiveness and support academic decision-making. However, issues such as data privacy, algorithmic bias, and limited AI literacy remain significant obstacles. Responsible integration of AI requires strong policy frameworks, institutional readiness, and transparent system design.